A Case of Primary Neuroendocrine Carcinoma of the Retroperitoneum - Fukushima, Mika (Hinyokika kiyo. Acta urologica Japonica, 2021)
In this case report, we describe a case of primary retroperitoneal neuroendocrine carcinoma. An 85- year-old man presented with a 3-week history of left back pain. Contrast-enhanced computed tomography showed an 8×5 cm mass to the left of the aorta and multiple hepatic metastases. Immunohistochemistry staining of the tumor cells showed positivity for the neuroendocrine marker synaptophysin and a very high Ki67 proliferation index. He was treated with carboplatin and etoposide. After 2 courses of chemotherapy, the mass had decreased in size, confirming that the treatment was effective. We plan to administer a total of 6 courses of chemotherapy